The impacts of low flow, ice-cover and ice thickness on sediment load in a sub-arctic river: Modelling sediment transport with particle image velocimetry calibration data sets - Pajunen, Virpi (John Wiley & Sons, 2025)
Climate change will be pronounced in sub-arctic and arctic regions. Consequently, a shorter ice-cover period, increased precipitation and changes in the timing and magnitude of discharge are expected. These hydroclimatic changes can have an impact on sediment transport in northern rivers. Studying spatial and temporal variation of the processes in low-flow open-water and ice-covered conditions is crucial to improve the prediction of future changes. The investigation of under-ice conditions has been challenging and new approaches for their measurement are much needed. We analyse the spatial sediment transport in a meandering subarctic river during different flow conditions, i.e., low flow open-channel during autumn and ice-covered during winter. We use one-dimensional (1D) morphodynamic models with image-based sediment transportation data sets. We also simulate sediment transport with different ice thicknesses to better understand the overall bedload transport in a subarctic river in mid-winter conditions.
Simulations for the studied meander bend showed a considerable flow-driven decrease of sediment transport in ice-covered conditions when compared to open-water conditions. Erosion was more pronounced in open-water conditions and deposition was the prevailing process in ice-covered conditions. When an additional increase in ice thickness was simulated, bedload increased, because the thicker ice narrowed the river channel substantially and thus leading to an increase in flow velocity and shear forces. Instead of solely relying on the sediment samples, the additional consideration of an image-based sediment data set enabled a more reliable model calibration in ice-covered conditions. This encourages further usage of image-based methods for sediment transport estimations, especially in ice-covered conditions. In the future, changes in river-ice can be expected to decrease under-ice sediment load but increase annual open-water sediment loads. The increasing summative sediment transport of small arctic and subarctic rivers can have significant consequences on the downstream waterbodies.